1935
DOI: 10.1152/ajplegacy.1935.112.2.351
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coronary Occlusion on Myocardial Contraction

Abstract: Many students of the coronary circulation must have noted that the ventricular zone affected by ligating a large coronary branch not only appears cyanotic and dilated, but that it seems to alter in its mode of contraction. The detailed and sequential changes in contraction are not easily followed by the unaided eye and so far have not been recorded myographically. The reasons for this were the lack of an adequate and suitable myograph and a technic for the application of one to a limited ventricular surface so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
199
1
3

Year Published

1937
1937
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,050 publications
(207 citation statements)
references
References 0 publications
4
199
1
3
Order By: Relevance
“…Relative to the first of these features, it has been demonstrated that within seconds after ligation of a major coronary artery, the affected myocardium will cease contracting normally and will actually bulge during systole. 19 In the second series, therefore, the alteration in distribution of blood flow evoked by higher intraventricular pressures may be attributable either to its effects upon the non-contracting myocardium, or to its influence upon collateral rather than cognate channels.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the first of these features, it has been demonstrated that within seconds after ligation of a major coronary artery, the affected myocardium will cease contracting normally and will actually bulge during systole. 19 In the second series, therefore, the alteration in distribution of blood flow evoked by higher intraventricular pressures may be attributable either to its effects upon the non-contracting myocardium, or to its influence upon collateral rather than cognate channels.…”
Section: Discussionmentioning
confidence: 99%
“…Correlating the echocardiographic and morphologic data for each myocardial slice, we identified three categories: (1) To test the null hypothesis that there is no di-fference in systolic wall thickening or motion between tissue that was infarcted, adjacent to infarction, and distant normal, separate two-way analyses of variance were performed using a general linear model for the dependent variables of thickening and motion. The independent factors were tissue morphology and dog.…”
Section: Analysis Of Datamentioning
confidence: 99%
“…Furthermore Gd is commonly used to interrupt stretch-mediated changes in intracellular ion flux in the heart through a presumed blockade of specific stretch-activated ion channels (22)(23)(24). Since mechanical stretch causes pathophysiologic changes in the myocardium (1,22,25,26), and regional myocardial ischemia results in abnormal stretch (2,27,28), the effects of Gd observed herein may also be related to modulation of ion fluxes that are caused by ischemia-induced stretch. Effects on K ATP and perhaps other ion channels may be of particular importance when Gd is administered one minute before reperfusion, as cell signaling to induce gene expression (as postulated above) would be a less likely factor in such a short time frame.…”
Section: Discussionmentioning
confidence: 90%